Influence of Various Tooth Shape Topology for Single-Phase Permanent Magnet Flux Switching Machine. Issue 1 (March 2021) - Jusoh, Laili Iwani; Sulaiman, Erwan; Ahmad, Md Zarafi; Soomro, Irfan Ali; Soomro, Hassan Ali
Abstract: Permanent magnet flux switching machine (PMFSM) has the advantages of solid design structure, high torque performances, and high efficiency. The method to increase performance and decrease the cost of the motor through a selection of numbers of slot and pole is a major issue that needs to be solved. Therefore, to further improve the electromagnetic torque, a novel 4-4S-8P multi-tooth, 4S-8P segmental-tooth and single-tooth PMFSM machine respectively is proposed based on the slot pole analysis performance. Hence, the performance is including the flux linkage, cogging torque, back-electromotive force (back-emf), output torque, and power performance. The results display that the various tooth shape topology have a large impact on the performance design. JMAG Designer version 14.3 under 2D finite element analysis (2D-FEA) are used to complete the analysis. The results show that the right combination of a single-tooth 4S-8P PMFSM structure is the best choice according to the high performance of torque analysis.